DIAGNOSTIC ACCURACY OF US-FNAC OF AXILLARY LYMPH NODES IN PATIENTS WITH PRIMARY BREAST CANCER USING SENTINEL LYMPH NODE BIOPSY AS STANDARD REFERENCE - Fayyaz, Muhammad Bilal; Niazi, Imran Khalid (Journal of Ayub Medical College Abbottabad, 2019)
Background: The advent of US guided FNAC in the investigation of adenopathy has become a suitable and commonly practiced minimally invasive procedure which is safe, simple, quick, highly cost effective and innocuous. Nowadays, in modern days FNAC is done in almost all cases due to its high specificity, Positive predictive value (PPV) and no complications resulting in fewer SNLB and directly proceeding with neo-adjuvant chemotherapy or ALND.Methods: A total of 160 females between ages 30-60 years who had clinical palpable breast lump, newly diagnosed cases of breast cancer with palpable axilla nodes were included. Patients who already received neoadjuvant therapy and whose biopsy does not yield enough specimens and needs repeat biopsy were excluded. All the patients were then undergoing ultrasound guided fine needle aspiration. Afterwards, all patients were gone through axillary surgery for the definite histopathology report. FNAC results were compared with pathology after SLNB. Results: Mean age was 46.61±8.75 years. In 67 FNAC positive patients, 61 were True Positive and 06 were False Positive. Among, 93 FNAC negative patients, 18 were False Negative whereas 75 were True Negative. Overall sensitivity, specificity, negative predictive value, positive predictive value and diagnostic accuracy of US guided FNAC of suspicious axilla nodes in patent with primary breast carcinoma was 77.22%, 92.59%, 80.65%, 91.04% and 85.0% respectively. Conclusion: This study concluded that US guided FNAC of suspicious axilla nodes in patient with primary breast carcinoma has quite acceptable diagnostic accuracy. Keywords: Breast malignancy; fine needle aspiration cytology; axillary lymph node dissection; Aentinel lymph node biopsy; sensitivity